Analysis of Demotivating Factors Affecting Students’ Willingness to Speak English - Pale, Erlinda Sonya; Wisrance, Maria Wihelmina (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The hesitation to speak English in the class was the crucial problem that occurred in semester seven students of the English Department of Timor University. This study figured out the discouraging points that influence the students' eagerness to speak English in the class, the most dispiriting factors, and the attempt that they executed to overcome their problem. The subject of the study was 30 semester seven students of the English Department of Timor University. The qualitative method was employed to analyze the data in this study. Interview and questionnaire were applied as the instruments to obtain the data. The result of the study pinpointed that there were internal and external factors that affect discouraging students in the classroom. The finding also revealed that the most demotivating factors which affected the students' willingness to communicate in English were motivation and confidence. The students also performed a few things to overcome their problems. The conclusion required the students to prompt themselves and be prompted by other people to pursue a good interaction in English.Keywords: demotivating, students, willingness